Kvalitetsledelse på danske hospitaler: Ledelsernes indflydelse på introduktion og vedligeholdelse af kvalitetsstrategier i det danske sundhedsvæsen - Anette Frey Larsen (Copenhagen Business School (CBS), 2010)
– The focus of this thesis is ”Quality Leadership in Danish Hospitals” and the conditions for good quality development on the operational level. Within this framework it is the objective of the thesis in three selected hospitals, geographically spread over the country, to investigate the view of the concept “quality” among department leaders from five referral centers and its impact on the department's quality work. The overall quality concept in the three hospitals is based on two different leadership technologies: Total Quality Management and Accreditation. Two of the hospitals have applied the TQM model as leadership technology but use the method in different ways. The third hospital applies Accreditation. Accordingly the three hospitals have organized in separate ways.....
hdl:10398/8064
Keywords: 650